STRUCTURAL EVOLUTION OF METAMORPHIC AND INTRUSIVE ROCKS FROM THE CENTRAL PART OF THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - トヨシマ, ツヨシ; オワダ, マサアキ; シライシ, カズユキ; TOYOSHIMA, Tsuyoshi; OWADA, Masaaki; SHIRAISHI, Kazuyuki (National Institute of Polar Research, 1995)
P(論文) Structural evolution of the central part of the Sør Rondane Mountains (SRM) is divided into seven stages, from D_1 to D_7,based on their characteristics of deformation, metamorphism and igneous activity. The metamorphic history of the central SRM is divided into three stages, prograde metamorphic peak stage, retrograde metamorphic stage related to its exhumation and contact metamorphic stage. The metamorphism of the former two stages has occurred not only with ductile deformation but also with various kinds of magmatic intrusions. The D_1 stage before the tonalite intrusion corresponds to the prograde metamorphic peak stage. The retrograde metamorphism and exhumation of the lower crustal rocks in the central SRM began at the D_2 stage, closely related to the tonalite intrusion and mylonitization. The D_2-deformation and subsequent D_3-mylonitization were caused by the top-to the SW to S and top-to the SE displacements, respectively, in extensional tectonic regimes. After these mylonite-forming tectonics, poly-stage folding occurred in compressional tectonic regimes. The NNE-SSW compressional stress acted after the D_3 stage, resulting in the WNW-ESE trending folds and minor thrusts with top-to the N sense. The SRM rocks during this stage were emplaced under the greenschist-facies condition. Subsequently, the E-W compressional stress worked during the D_5 stage, and then NW-SE compression during the D_6 stage. Granites and syenites intruded in the last stage. Strain-free quartz ribbon and random-oriented kyanites and biotites might have been produced by the contact metamorphism with the non-foliated 500Ma granites. departmental bulletin paper